PENERAPAN POMPA HYDRAM PARAREL UNTUK MENGATASI PERMASALAHAN AIR BERSIH DI DESA KESIMPAR-KARANGASEM - Tenaya, IGN. Putu; Sukadana, IGK; Wirawan, IKG. (Buletin Udayana Mengabdi, 2016)
Kesimpar village located in the district Abang, regency of Karangasem. Consists of 2750 inhabitants, of which 95 percent are farmers and ranchers. To meet the water needs from Andong water resources has capacity 10 liters per second, with a walk takes 2-3 hours. From the initial survei and mapping of the situation by the team, accompanied by community leaders, it is possible to build clean water sistems with application technologist hydram pump. Tim from Mechanical Engineering of Udayana University ready to help designing and assisting in building the sistem. The target of this service are: the establishment of water services, distribution evenly to every community with the appropriate discharge national standards. Resulting from the implementation of activities: Village Kesimpar clean water source that has the potential to be fully utilized. It was decided to use hydram pump valve tap spherical models, the dimensions of the pump: pump body diameter 6 inch, 8 inch diameter of air tube, diameter/length drive pipe 6 inch/54 m. The execution of the planned sistem is evidenced by pumping beats period 40-44 perminute. Evaluation of the pumping capacity has reached capacity planning, one pump has a capacity of 0.9 - 1.0 liters/minute, and two pumps are installed in parallel has a total capacity of 1.8 - 2.0 liters/min. Residents in the area Pura Bangun Sakti some 50 families had served with clean water.